2020
DOI: 10.1007/s40124-020-00226-5
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Simulation for Pediatric Critical Care Medicine

Abstract: Purpose of Review This review highlights the emerging fields of simulation research by tying innovation into principles of learning and process improvement. Recent Findings Advances have been made in both educational simulation and simulation for quality improvement, allowing this versatile modality to be more broadly applied to healthcare and systems. Summary Simulation in pediatric critical care medicine continues to evolve. Although the majority of simulation is focused on learner education, emerging resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 99 publications
0
2
0
Order By: Relevance
“…Although there are a limited number of studies available on the topic and it is difficult to isolate the effects of simulation, Goldshtein found that the implementation of in situ simulation in training programs improves patient morbidity and/or mortality (Goldshtein et al, 2020). Therefore, simulation positively impacts standards of care by improving health professionals' performance (Harwayne-Gidansky et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although there are a limited number of studies available on the topic and it is difficult to isolate the effects of simulation, Goldshtein found that the implementation of in situ simulation in training programs improves patient morbidity and/or mortality (Goldshtein et al, 2020). Therefore, simulation positively impacts standards of care by improving health professionals' performance (Harwayne-Gidansky et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These include translational simulation to prepare health services for the COVID-19 pandemic [ 18 30 ], for hospital relocation or physical space testing [ 31 ], for clinical pathway or process testing [ 32 39 ], and for shaping culture and teamwork in healthcare settings [ 35 , 40 46 ]. Other citing literature has included conceptual discussions and review articles [ 47 51 ], as well as efforts to develop methods and tools for ‘translational simulation in action’ [ 16 , 32 , 52 ]. We now consider and critique these examples and provide a summary in Table 1 .…”
Section: Exploring Translational Simulation In Practicementioning
confidence: 99%
“…Simulation education is commonplace within PICU and physiotherapy, where real patient encounters are substituted with artificial models, actors or virtual reality patients. Simulation enables the learner to engage in a safe environment, and provides hands-on learning in an immersive environment, with opportunities for repetition, practice and feedback (Harwayne-Gidansky et al, 2020). A video of a simulated patient assessment and treatment was used in this study as this was more readily available and offered fewer challenges related to patient confidentiality, when compared to a real patient video.…”
Section: Focus Group Structurementioning
confidence: 99%